Effect of Water and Soil Contamination by Heavy Metals in Lettuce (Lactuca sativa), Cabbage (Brassica oleracea var. capitate), and Turnip (Brassica napus L.) at Different Stage - Nibret Mekonen; Girum Habte (Annals of Environmental Science and Toxicology - Peertechz Publications, 2022)
Environmental pollution with heavy metals is very harmful to the human body and other life forms, even in low concentrations, as there is no effective removal mechanism. Urban agriculture utilizes this contaminated land for the cultivation of vegetable crops to facilitate their food security and entry of toxic heavy metals into the food chain. The objective of this study was to evaluate the impact of contaminated soil and water with heavy metals on the quality of vegetable crops at different growth ages. Microwave Plasma Atomic Emission Spectrometry (MP-AES) was used to determine the concentration of these heavy metals. The concentration of heavy metals (Fe, Mn, Zn, Cu, Co, Ni, Pb, and Cr) in contaminated soil was found to be 39434.9±30.0, 3183.7±43.5, 222.0±10.2, 22.28±2.5, 0.057±0.00, 5.8±0.03, 72.72±0.01, 148.6±15 mg/kg, respectively. In addition, the mean concentration of Fe, Mn, Zn, Cu, Co, Ni, and Cr in wastewater was found to be 5.2±0.5, 0.8±0.08, 0.72±0.01, 1.05±0.03, 0.01±0.00, 0.2±00, 0.72±0.01 and 0.14±0.02, respectively. The relative abundance of heavy metal in soil, water and vegetable samples were in the following order: Fe >Mn >Zn > Cr > Pb> Cu> Ni> Co, Fe > Cu > Mn >Zn =Pb> Ni > Cr > Co and Fe >Mn >Zn > Pb > Cu> Cr > Ni> Co, respectively, and the accumulation of heavy metals in three month growth. All lettuce, cabbage, and turnip vegetables grew faster than two months. Both two and three months of age, the accumulation of heavy metals in turnips > lettuce > cabbage. Most of the soil, water, and vegetable samples exceeded the permissible limit of heavy metals prescribed by the World Health Organization (WHO) standards.